Human Alpha Galactosidases Transiently Produced in Nicotiana benthamiana Leaves: New Insights in Substrate Specificities with Relevance for Fabry Disease - Kytidou, Kassiani; Beenakker, Thomas J. M.; Westerhof, Lotte B.; Hokke, Cornelis H.; Moolenaar, Geri F.; Goosen, Nora; Mirzaian, Mina; Ferraz, Maria J.; de Geus, Mark; Kallemeijn, Wouter W.; Overkleeft, Herman S.; Boot, Rolf G.; et al. (Frontiers in Plant Science, 2017)
Deficiency of α-galactosidase A (α-GAL) causes Fabry disease (FD), an X-linked storage disease of the glycosphingolipid globtriaosylcerammide (Gb3) in lysosomes of various cells and elevated plasma globotriaosylsphingosine (Lyso-Gb3) toxic for podocytes and nociceptive neurons. Enzyme replacement therapy is used to treat the disease, but clinical efficacy is limited in many male FD patients due to development of neutralizing antibodies (Ab). Therapeutic use of modified lysosomal α-N-acetyl-galactosaminidase (α-NAGAL) with increased α-galactosidase activity (α-NAGALEL) has therefore been suggested. We transiently produced in Nicotiana benthamiana leaves functional α-GAL, α-NAGAL and α-NAGALEL enzymes for research purposes. All enzymes could be visualized with activity-based probes covalently binding in their catalytic pocket. Characterization of purified proteins indicated that α-NAGALEL is improved in activity towards artificial 4MU-α-galactopyranoside. Recombinant α-NAGALEL and α-NAGAL are not neutralized by Ab-positive FD serum tested and are more stable in human plasma than α-GAL. Both enzymes hydrolyze the lipid substrates Gb3 and Lyso-Gb3 accumulating in Fabry patients. The addition to FD sera of α-NAGALEL, and to a lesser extent that of α-NAGAL, results in a reduction of the toxic Lyso-Gb3. In conclusion, our study suggests that modified α-NAGALEL might reduce excessive Lyso-Gb3 in FD serum. This neo-enzyme can be produced in Nicotiana benthamiana and might be further developed for the treatment of Fabry disease aiming at reduction of circulating Lyso-Gb3.